Effectiveness of slurry wall for lead retention in contaminated soil - C. Teerawattanasuk; P. Voottipruex (International Association of Lowland Technology, 2017)
This paper examines the hydraulic conductivity and strength properties of several bentonitecement (BC) mixtures and to delineate the influence of the cementitious material content, bentonite, and curing time upon the strength and hydraulic conductivity of BC barrier materials. The two ratios of cementitious material to bentonite-water slurry used were 7.5%, and 15%. Samples were cured for a period of 7, 14 and 28 days at 100% humidity, after which samples of each mixture underwent permeability and unconfined compression testing. It can be seen that unconfined compressive strength (qu) of specimen increased as cement content increased due to the hydration products. However, the qu of specimen decreased as bentonite content increased due to high expansion. Specimens with high cement content form a low permeability material that keeps high lead contaminant in top and middle portion in the specimen. The results shows that qu increase as cement content and curing period increase while the permeability coefficient decrease as curing period and cement content increase. Moreover, the effectiveness of slurry wall for lead retention contaminated soil can be obtained by using the optimum bentonite-cement proportion of B10C15.